Pendampingan Revitalisasi Pembangunan Sekolah Dasar di Kota Jayapura dan Kabupaten Sarmi - Deliana Mangisu; Herlina Sanggamele; Erwin Erwin; Ardyansah Syukri (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
This community service activity aims to support the revitalization of elementary schools in Jayapura City and Sarmi Regency by assisting the implementation of school construction and rehabilitation programs. The support provided included the preparation of technical documents, construction supervision, and monitoring and evaluation of each stage of the school revitalization process. The activity was conducted through several methods, namely initial preparation, field surveys, implementation assistance, and monitoring and evaluation. During the preparation stage, the team coordinated with relevant stakeholders and reviewed the technical requirements of each school. Field surveys were then carried out to identify actual conditions, construction needs, and potential implementation challenges. The implementation stage focused on ensuring that construction activities followed the approved technical plans, quality standards, and work schedules. Monitoring and evaluation were conducted to assess progress, identify obstacles, and provide recommendations for improvement. The results show that the school revitalization construction activities generally proceeded according to plan, although several challenges were encountered, particularly unfavorable weather conditions and limitations in the availability of construction materials. Overall, this initiative is expected to strengthen the quality of school construction management, improve the safety and functionality of educational facilities, and contribute to better standards of elementary education in both regions.